Clinical manifestations, toxicities, and outcome of two children with Nijmegen breakage syndrome and lymphoid malignancies – case reports - Filipiuk, Aleksandra; Kozakiewicz, Agata; Kośmider, Kamil; Karska, Katarzyna; Lejman, Monika; Zawitkowska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Nijmegen breakage syndrome (NBS) is a rare disease with an autosomal recessive pattern of inheritance caused by mutations in the NBN gene. We report 2 patients with NBS and T-cell lymphoblastic lymphoma (T-LBL), in whom diagnosis and therapy were difficult challenges. Both patients were diagnosed with NBS by mutation analysis of the NBN gene, which revealed homozygosity for a typical 5 base pair deletion (657del5). The lymph node biopsy revealed T-LBL, and both patients were treated according to EURO-LB 02. Complete remission was achieved in the first patient. In the second case, bone marrow relapse was observed, and the patient died due to disease progression. In conclusion, patients with NBS should be closely monitored because of a higher frequency of lymphoma than in the general population. The described cases indicate the importance of identifying predictive markers of cancers and developing treatment regimens for patients with NBS and malignancies.